REDUCTION OF CHROMIUM LEVELS IN TANNING WASTEWATER BY PHYTOREMEDIATION METHOD: A REVIEW - Dwi Astuti; Acintya Wedaning Agni Janametri; Sri Darnoto; Rezania Asyfiradayati (CV KULTURA DIGITAL MEDIA, 2022)
Introduction: Chromium content in tannery wastewater causes environmental health problems if the waste is not treated correctly, one of which is phytoremediation using various types of aquatic plants (water hyacinth, apu wood, horn moss, and Lemna sp.).This study aimeds to find the types of aquatic plants that most reduce the levels of Cr in tannery wastewater. Method: research using a literature study design that uses a database, Pubmed, Google Scholar, and Science Direct starting in 2011 to 2021 for analysis. The keywords used Indonesian and English search keywords are degradation, wastewater, tanning, aquatic plants, phytoremediation, water hyacinth, apu wood, water spikes, fisheye, and hornworts. The inclusion criteria included the dependent variable from the study, namely the decrease in Cr levels, the independent variables inc; the types of aquatic plants, accessible full text, experimental quantitative methods, journals published with ISSN or SINTA 1-6 or Scopus, and exclusion criteria include paid and inaccessible journals in full as well as the year of publication of articles before 2011. Result: all journals succeeded in reducing Cr levels in tannery wastewater within a contact time of 3 hours; 5 minutes; 10 minutes; 15 minutes; 5 days; 7 days; 14 days; 15 days; 25 days; and 28 days. This research shows that this research shows lower Cr levels in tannery wastewater. Conclusion: the types of aquatic plants tThehe most Cr levels in leather tanning wastewater are water hyacinth plants with a contact time of 3 hours; 5 minutes; 10 minutes; 15 minutes; and 28 days. Therefore, phytoremediation needs to monitor the growth and selection of aquatic plant species adapted to the environment so that phytoremediation can provide maximum results in the absorption, removal, and reduction of heavy metals harmful to environmental health.